GAYA DAKWAH DAN RETORIKA BUYA SYAKUR DALAM KONTEKS DAKWAH KONTEMPORER - Utomo, Pujo (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2023)
Buya Syakur's preaching style and rhetoric are examples of effective religious communication in dealing with fanaticism, literalism, and extremism issues in contemporary society. As a moderate cleric, Buya Syakur is known to combine rationality, humor, and logical argumentation in his sermons, so that Islamic teachings are delivered contextually and easily understood by various groups. This study uses a descriptive qualitative method with Norman Fairclough's critical discourse analysis model to identify the application of ethos (credibility), pathos (emotion), and logos (logic) elements in Buya Syakur's rhetoric. The results of the analysis show that Buya Syakur's sermons are not only persuasive, but also a form of criticism of rigid and textual religiosity. Through humor, logic, and a contextual approach, he builds a moderate Islamic narrative that is relevant to the needs of modern society and effective in rejecting extremism and prioritizing tolerance, justice, and humanitarian values. Keywords : Buya Syakur, Rhetoric, Contemporary Preaching, Fanaticism, Literalism, Extremism Issues